Preventing Ischemic Cerebrovascular Events in High-Risk Patients With Non-disabling Ischemic Cerebrovascular Events Using Remote Ischemic Conditioning: A Single-Arm Study - Liu, Shimeng; Gao, Zongen; Meng, Ran; Song, Haiqing; Tang, Tianping; Zhao, Ya; Chen, Rong; Sheng, Yanzhen; Fan, Qianqian; Jiang, Fang; Zhang, Qian; Ding, Jianping; et al. (Frontiers in Neurology, 2021)
Background: Secondary stroke prevention after a high-risk, non-disabling ischemic cerebrovascular event needs to be enhanced. The study was conducted to investigate whether remote ischemic conditioning (RIC) is effective in preventing recurrent ischemic events within 3 months. Methods: This was a four-center, single-arm, open-label Phase IIa futility trial (PICNIC-One Study). Adult patients (≥18 years of age) who had an acute minor ischemic stroke (AMIS) with a National Institutes of Health Stroke Scale score ≤ 3 or a transient ischemic attack (TIA) with moderate-to-high risk of stroke recurrence (ABCD score ≥ 4) within 14 days of symptom onset were recruited. Patients received RIC as adjunctive therapy to routine secondary stroke prevention regimen. RIC consisted of five cycles of 5-min inflation (200 mmHg) and 5-min deflation of cuffs (45 min) on bilateral upper limbs twice a day for 90 days. Results: A total of 285 patients met the study criteria, of which 167 provided signed informed consent and were enrolled. Data from 162 were analyzed with five subjects excluded. Recurrent AIS/TIA occurred in 6/162 (3.7%) patients within 3 months, with no occurrence of hemorrhagic stroke. The top three adverse events were upper limb pain (44/162, 27.2%), petechia (26/162, 16.0%), and heart palpitation (5/162, 3.1%). About 68 (42.0%) subjects completed ≥ 50% of 45-min RIC sessions. Conclusions: RIC is a safe add-on procedure and it has a potential benefit in reducing recurrent cerebrovascular events in patients with high-risk, non-disabling ischemic cerebrovascular events as the risk of stroke/TIA events is lower than expected; however, its compliance needs to be improved. Our study provides critical preliminary data to plan a large sample size, randomized controlled clinical study to systematically investigate the safety and efficacy of RIC in this population.